2021
DOI: 10.1177/14604086211002583
|View full text |Cite
|
Sign up to set email alerts
|

The potential benefits of enzymatic debridement in multi-casualty burns incidents

Abstract: Bromelain-based enzymatic debridement (ED) is a topical treatment that is growing in popularity for the non-surgical management of burn wounds. Although initially used for small injuries, experience has grown in using it for burns >15% Total Burns Surface Area (TBSA). A household explosion resulted in burns to multiple patients, with four requiring burn wound debridement. This case report demonstrates their management using ED. Four adult male patients were treated with ED, mean age 38.4 years. Their injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Bowers et al advocated that BMCEs could be successfully managed with BBD in their experience of a house explosion with five patients 60 . Kiely et al reported a similar experience in a house explosion with 4 patients 95 …”
Section: Discussionmentioning
confidence: 99%
“…Bowers et al advocated that BMCEs could be successfully managed with BBD in their experience of a house explosion with five patients 60 . Kiely et al reported a similar experience in a house explosion with 4 patients 95 …”
Section: Discussionmentioning
confidence: 99%